EXAMINING THE MODERATING ROLE OF ASSET TANGIBILITY IN THE LEVERAGE PERFORMANCE RELATIONSHIP OF NIGERIA’S INDUSTRIAL GOODS SECTOR - Agbeyinka Yinka Ibrahim (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
This study investigates the moderating role of asset tangibility in the relationship between capital structure and firm performance among listed industrial goods firms in Nigeria over the period 2014 to 2023. Drawing on pecking order and trade-off theories, the research evaluates whether varying debt compositions, such as the short-term debt, long-term debt, total debt, and debt-to-equity ratios, affect financial performance (proxied by return on assets) differently depending on the level of tangible assets. Panel data derived from audited financial reports of 10 firms were analyzed using Generalized Least Squares (GLS) random effects estimation. The findings indicate that neither leverage variables nor their interactions with asset tangibility exert statistically significant effects on firm performance. These outcomes suggest that, within Nigeria’s industrial goods sector, asset tangibility alone may not enhance the efficiency of debt utilization. The study contributes to capital structure literature by contextualizing firm-specific attributes in emerging markets and underscores the need for more nuanced financial strategies and supportive regulatory frameworks.